PERSONAL TRAINING TRAITS, TRAINING COMPETENCE AND MOTIVATION AS PREDICTORS TO SPORTS PERFORMANCE OF PARALYMPIADA ATHLETES IN NEGROS ISLAND (PHILIPPINES) - Janette Canizares Magalona (Program Pascasarjana Universitas Negeri Jakarta, 2020)
Abstract. The study aims to assess the relationship of Personal Training Traits (PTT), Training Competence (TC), and Motivation (M) to the Performance (P) Levels of paralympiada athletes. The method used in this study were path analysis; multiple correlations; the coefficient level of determination; Kolmogorov Smirnov for normality test and; ANOVA. A total of 105 paralympiada athletes with parent’s approval participated in the study. The results of the investigation concluded that: (1) There was no direct correlation on the PTT and P, the PTT and TC , the PTT and M (2) There was a direct correlation on the TC and the P, the M and the P , the TC and M ; The following conclusions were drawn: Training Competence is essential to ensure better performance among paralympiada athletes. However, it is not the only measure in winning a competition. A direct correlation of Motivation to Sports Performance was strongly revealed. The direct influence of Training Competence to Sports Performance was indicated. Thus, it is recommended to professionalize the trainings of paralympiada athletes. Keywords: Motivation, Paralympiada, Personal Training Traits, Sports Performance,Training Competence